Preparation of Poly (N- Imidazolyl maleamic acid) - Ali, Firyal M; Kadem, Khudheyer J; Rahi, Firas A; Gayadh, Estabrak W (Al-Nahrain Journal of Science, 2014)
In this research preparation of poly (maleamic acide) which substituted with imidazole as a bioactive material is performed. It was prepared from reaction of maleic anhydride with imidazole and Ring opening of maleic anhydride by imidazole, then the substituted maleamic acid was polymerized by freeradical polymerization by using dibenzoylperoxide as initiator. The structure of synthesized polymer was confirmed by FTIR, UV. and 1H-NMR spectroscopes, The controlled release of imidazol units was studied in different pH values at 37 0C. All physical properties of prepared polymer were measured.